DRESS CODES IN SCHOOLS: A TALE OF HEADSCARVES AND HAIRSTYLES - Fatima Osman; Jean Wilké (Obiter, 2018)
In 2016 independent or private schools made headlines as learners protested the codes of conduct of various schools and the lack of accommodation of African hairstyles. The question of a school’s autonomy to enact a code of conduct and prohibit certain religious or cultural dress is not new and there has been worldwide controversy regarding schools banning the Islamic headscarf. This article examines the obligation of South African public and independent schools to accommodate the headscarf and diverse hairstyles. It argues that the Islamic headscarf is a central tenet of the Islamic faith protected by the constitutional right to religious freedom and that given the current guidelines on school uniforms, public schools are bound to accommodate the headscarf. The matter is more nuanced with independent schools that may be established in the pursuit of a religious ethos. The article argues that independent schools are equally prohibited from discrimination on religious and cultural grounds and must demonstrate the justifiability of the lack of accommodation. While these bans may be allowed, the historical inequalities in education and the socio-economic context in which the provision of excellent education still favours certain races must be weighed carefully against the school’s religious vision. Hairstyles are a more complex matter given their diversity. The article argues that disputes as to whether a hairstyle forms part of a culture are likely to become difficult given the porous and evolving nature of culture. Public and independent schools are rather urged to re-evaluate their codes of conduct. Codes that favour Eurocentric notions of neatness may indirectly discriminate on race, a completely untenable situation in a constitutional South Africa. These codes must be revised to celebrate and affirm our diversity rather than be used to exclude and alienate segments of society.